Assessment of hand hygiene practice among residents of Uyo-southern Nigeria during the COVID-19 pandemic - Ubani, Blessing Chinenye; Ekuma, Agantem Emmanuel; Akpabio, Akpabio Akanimo; Akpabio, Tiemah Ntiense (International Journal of Infection Control, 2020)
The COVID19 pandemic has caused widespread global devastation with over 11 million infections and 534,000 deaths recorded at the end of June 2020. Measures such as physical distancing and regular hand hygiene are effective in controlling the disease, though compliance varies. This study aimed to determine the frequency of hand hygiene compliance, identify reasons for non-compliance as well as significant associations of hand hygiene performance, type and duration. Visitors to two landmark sites in Uyo—southern Nigeria, (a tertiary hospital and a popular mall) were observed for hand hygiene compliance. The type and duration of hand hygiene was also assessed. A subset of the participants was subsequently invited to participate in an interviewer-administered survey comprising questions on hand hygiene frequency, type, duration and reasons for non-compliance. Ethical approval was obtained for the study. A total of 490 subjects were observed from both sites (280 from the mall and 210 from the hospital), while 155, comprising 52.9% females and 47.1% males, with a mean age of 32.3 ± 11.2 years completed the survey. Although almost all patients (94.2%) considered hand hygiene a necessity, most (65.2%) forgot to wash their hands. Majority of the participants (74.3%) performed hand hygiene, while using soap and running water was the preferred method in majority (80.6%). Age and location were significantly associated with hand hygiene performance, type and duration Over 70% of adult residents in Uyo performed hand-hygiene though infrequently. Forgetfulness was the most common reason for non-compliance. Public education and compulsion at public places are key strategies in improving hand hygiene compliance.